Finger flexion to extension ratio in healthy climbers: a proposal for evaluation and rebalance - Marine Devise; Léo Pasek; Benjamin Goislard De Monsabert; Laurent Vigouroux (Frontiers Media S.A., 2023)
IntroductionFinger strength is a key factor in climbing performance and is highly dependent on the capacity of the finger flexor muscles. The majority of finger-specific training therefore focuses on improving such capabilities by performing finger flexion contraction during hanging exercises on small holds. However, greater strength in the finger flexors causes an imbalance with the extensor muscle capacities. Such an unfavourable imbalance may be detrimental to finger strength and could possibly lead to an increase in the risk of finger injury. The aim of this study was to develop an easily implementable method to assess the flexor-to-extensor imbalance and evaluate the effects of different training on it.MethodsSeventy-eight experienced climbers were tested to assess their maximum finger flexion strength (MFS), maximum finger extension strength (MES) and MFS/MES ratio. Fifty-two of them were randomly assigned to one of three training regimens: intermittent static flexion at 80% MFS (TFlex; n = 11), intermittent static extension at 80% MES (TExt; n = 10), intermittent repetition of alternating flexion and extension (TPaired; n = 11) or no specific training (CTRL; n = 20). They trained twice a week for four weeks on a hangboard. Before and after training, force data were recorded on a force-sensing hangboard and MFS, MES and the MFS/MES ratio were compared using ANCOVA.ResultsThe mean value of the MFS/MES ratio was 6.27 (confidence interval: 5.94-6.61) and the extreme ratio was defined above 8.75. Concerning the training intervention, no difference was observed in the CTRL group between pre- and post-tests. MFS improved significantly in the TFlex (+8.4 ± 4.4%) and TPaired (+11.9 ± 10.5%) groups, whereas MES increased significantly in the TExt group (+41.4 ± 31.3%). The MFS/MES ratio remained statistically stable among all groups (+0.9 ± 17.5% in TFlex, −1.9 ± 16.1% in TPaired), although the TExt group showed a decreasing trend (p = 0.1; −27.8 ± 17.6%).DiscussionThese results showed that only the extensor-based training had an effect on finger extension strength and the potential to rebalance the MFS/MES ratio.